Features of indicators of high-qualified tennis service acceptance at US Open 2020, ATP final tournament 2020 and Australian Open 2021 - Al Khalili, M.; Stepanova, M. E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identifying the number of indicators and the versatility of serving reception among the top eight tennis players in the world in 2020 according to the results of the rating of the Association of Tennis Professionals (ATP).